Instructional Orchestra Mediated with Montesory Media for Teaching English Vocabulary for Kindergarten Students - Degeng, Putu Dian D. (EDUCAFL : E-Journal of Education of English as a Foreign Language, 2012)
This article summarizes the design of instructional orchestra model based on Montessori media for English vocabulary acquisition for kindergarten students. It aims at fulfilling the need of instructional orchestra based on Montessori media which is designed using flexible model to stimulate creativity the motivation to learn for kindergarten, especially, meet the need of Griya Adinda Kindergarten students in learning English vocabulary. The instruction is developed by using 2 Dimensions of Degeng Instructional Orchestra. The products assessed by an instructional content expert, an instructional media expert, an instructional designer, kindergarten Headmaster, and a kindergarten teacher. Instruments used for data collecting were direct comment on the product script taken from instructional content expert and five-scale questionnaire taken from instructional media expert, instructional designer, kindergarten headmaster and kindergarten teacher. Products revision was done as the advises given by the experts, kindergarten headmaster and kindergarten teacher. Recommendations are given related to: product utility, product dissemination and further product development.Keywords: instructional orchestra, Montessori media, English vocabulary acquisition, kindergarten